INFLUENCE OF S. TYPHI LIPOPOLISACCHARIDE UPON EPITHELIZATION OF SKIN WOUNDS AND EPIDERMAL GROWTH FACTOR SECRETION - A. V. Kostarnoy; D. Yu. Logunov; L. V. Verkhovskaya; P. G. Gancheva; B. S. Naroditsky (Медицинская иммунология, 2014)
Abstract. Influence of topical application of bacterial lipopolysaccharide (LPS), a Toll-like receptor 4 agonist, upon epithelization process was investigated, using a murine incisional skin wound model. It was shown that topical LPS application accelerates wound epithelization, and this process was associated with increased levels of epidermal growth factor secretion in wounded skin area.